NAVIGATING THE SPECTRUM OF HUMANITY IN AS BRIGHT AS HEAVEN (2018) BY SUSAN MEISSNER - Ilham Ali, Muhammad; Ismail, Ismail; Pabur, Herminus Efrando (Journal Albion : Journal of English Literature, Language, and Culture, 2024)
This research aims to analyze the social situations and interpret quotes that express the social conditions and human value as reflected in the novel "As Bright as Heaven" amid the pandemic and World War 1. In this research, the writer used a qualitative method with a sociological approach. The primary data was collected from the novel, and the secondary sources were journals, e-books, and internet references. This research concludes that " As Bright as Heaven” is a novel exploring seven social situations. There were feelings, human values, hope and hopelessness, romance, death, moving, and after the pandemic. In each chapter, Meissner describes social situations based on their respective characters. Susan Meissner creates an emotionally rich and exciting story in this novel that highlights the strength of human beings in the face of tragedy through the characters' experiences and emotions.